The role of oral English proficiency of the local tour guides in promoting Aceh Tsunami Museum - Sofyan A Gani; Cut Intan Damayanti (Proceedings of AICS - Social Sciences, 2017)
This research aimed to find out the English language proficiency of the local tour guides of Aceh Tsunami Museum and the difficulties they faced in communicating with tourists. A qualitative descriptive research design was utilized to collect data in which the proficiency English tests and interviews were used as the instruments.  Based on the research results, only one out of 13 tour guides was in the excellent category in all speaking aspects (excellent in grammar, vocabulary, comprehension, fluency and pronunciation), while the other 12 tour guides are in the category of very good, good, and enough. Mostly, the difficulties faced by the tour guides of Aceh Tsunami Museum in speaking English are on expressing ideas verbally, lack of vocabulary, lack of grammar knowledge and poor pronunciation which makes them unconfident to speak English.